The role of electronic medical records in facilitating patient-centered care: A systematic literature review - Pamudji, Clarissa Rayna Savealty; Kusumo, Mahendro Prasetyo (Edelweiss Applied Science and Technology, 2025)
There has been a growing focus on improving patient-centeredness and advancing electronic medical records in recent years. Patient-centered care involves delivering healthcare tailored to the individual needs of patients. Therefore, electronic medical records are essential for enabling patient-centered treatment by providing healthcare practitioners with easy access to patients' information. The objective of this study is to systematically review research that has empirically assessed the impact of electronic medical records on promoting patient-centered care, specifically from the patients' perspective. The research methodology employed in this study is the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. The keywords used in the search included electronic medical record, patient-centered care, and patient satisfaction. A search was conducted across three electronic databases. The inclusion criteria encompassed publications from 2014 to 2023, full-text papers, open access articles in English that focused on the deployment of electronic medical records from the patients' perspective. Twenty-eight journals meeting these criteria were analyzed. The findings suggest that electronic medical records have a positive impact on promoting patient-centered care through improved information exchange between clinicians and patients. To further enhance patient-centered care services, it is necessary to customize electronic medical records according to the specific needs of each individual patient. The disparity in patient satisfaction rates between individuals who utilized electronic medical records and those who used paper-based records is not significant.